MENINGKATKAN AKTIVITAS BELAJAR, KETERAMPILAN KERJASAMA, BERPIKIR KRITIS, DAN HASIL BELAJAR MENGGUNAKAN MODEL CANGKAL DAN MEDIA WORDWALL MUATAN BAHASA INDONESIA PADA SISWA KELAS V SDN SUNGAI MIAI 8 BANJARMASIN - Fahrizal, Muhammad Rizki; Dwitalia Sari, Dessy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low levels of student activity, collaboration skills, critical thinking, and learning outcomes in Grade V of SDN Sungai Miai 8 Banjarmasin. These issues were caused by one-way teaching, minimal interaction, lack of varied instructional models and media, and a monotonous classroom atmosphere. The purpose of this research was to describe teacher activity and analyze improvements in student engagement, collaboration skills, critical thinking, and learning outcomes through the implementation of the CANGKAL model using Wordwall media. This Classroom Action Research (CAR) was conducted over four meetings in the second semester of the 2024/2025 academic year, involving 14 students. The study used a qualitative approach, with data collected through observations of teacher and student activities, and written tests to assess learning outcomes, collaboration, and critical thinking skills. The findings showed improvements in all observed aspects. Teacher activity reached the